Health education group with preschool children: Experience report of nursing students - Hunger, Leandra Lia Muller; Hesler, Lilian Zielke; Dutra, Luciana Maciel; Lima, Maria Eduarda Rosa de; Rodrigues, Nátali Gonçalves; Baldessarini, Thauana (Seven Editora, 2023)
The school environment is ideal for developing health education actions, which seek to teach and expand the knowledge of healthier daily practices. Thus, the objective of this report was to describe the experience of nursing students facing an educational action on oral hygiene for preschool children. This is a descriptive experience report produced through the experience with children aged 4 to 5 years from a school in the city of Santo Ângelo. The educational action was carried out by nursing students during the discipline of Collective Health Nursing I in the second semester of 2022. The activity was developed with 24 children of early childhood education on oral health and the importance of tooth brushing with the use of an educational theater and a practice accompanied by tooth brushing. Nurses have an important role in health education, as they propose new methodologies and interventions to face health problems that affect populations. Health education aimed at children allows learning, integration, and stimulation to do the correct brushing of the teeth, preventing future problems. DOI:https://doi.org/10.56238/ptoketheeducati-004